SIMULTANEOUS DETERMINATION OF BENZYDAMINE HYDROCHLORIDE, METHYLPARABEN AND PEPPERMINT OIL IN A SPRAY DOSAGE FORM BY GAS CHROMATOGRAPHY - CHORNYI, VASYL A.; GEORGIYANTS, VICTORIYA A.; GUREEVA, SVITLANA N.; CHORNA, OLGA V. (International Journal of Applied Pharmaceutics, 2019)
Objective: To develop and validate an analytical procedure for simultaneous determination of benzydamine hydrochloride, methylparaben and peppermint oil in a spray dosage form by gas chromatography method (GC). Methods: The analytical method was conducted on Agilent 7890 gas chromatograph, equipped with HP-5 capillary column with helium as a mobile phase, split/splitless injector and flame ionization detector and an auto injector. Validation parameters, such as selectivity, linearity, precision, accuracy and, robustness were estimated. Results: A method for simultaneous determination of benzydamine hydrochloride, methylparaben and peppermint oil in a spray dosage form by GC was developed. The retention time of menthol (marker substance of peppermint oil) methylparaben and benzydamine hydrochloride, was 5.0, 9.2, and 19.4 respectively. Relative standard deviation (RSD)% for precision was 0.24, 0.13 and 0.12 respectively. The linearity of the method for given analytes was estimated in a concentration range of 80-120% to a nominal concentration with the respective correlation coefficients of more than 0.999. Accuracy of the method was within 98-102% for all analytes. Conclusion: The developed analytical procedure meets the acceptance criteria of validation parameters and can be used in quality control laboratories for determination of benzydamine hydrochloride, methylparaben and peppermint oil in a spray dosage form.